Employee Attendance at Getasan District Head Office Information System Governance Design Using the COBIT 2019 Framework - Purcristhian Echy Candra; Melkior N. N. Sitokdana (Journal of Computer and Information Systems Ampera, 2025)
The Getasan sub-district office is a community service office, especially in the Getasan area, which still uses a manual attendance system starting from employee attendance, employee home attendance and employee attendance reports. So, during the recording process, errors may occur, or reports may be less accurate and there may be delays in finding the required data. The research method used is the prototype method. This employee attendance information system is a web-based system. By using this system, the attendance information system will run better than the manual system so that it can run more effectively and efficiently and the system will also be more conducive and improved when compared to the previous system. Apart from that, the best solution is to use a computerized system that can solve the problems that exist in this office, to achieve activities that support office activities.